Antiepileptic Drug Management in Hospitalized Epilepsy Patients With Nil Per Os Diets: A Retrospective Review. (April 2019) - Bank, Anna M.; Lee, Jong Woo; Ehlert, Alexa N.; Berkowitz, Aaron L.
Background and Purpose: Antiepileptic drug (AED) management in patients with epilepsy who cannot take their usual oral medications is a common neurologic dilemma in the hospital setting. Strategies to maintain seizure control in patients with nil per os (NPO, nothing by mouth) diet orders include continuation of oral AEDs despite NPO nutrition orders, administration of intravenous AED(s), or temporary administration of benzodiazepines. The frequency with which these strategies are used and their effectiveness in preventing in-hospital seizures is unknown. Methods: We conducted a retrospective cohort study to determine AED management strategies and seizure frequency in hospitalized epilepsy patients with NPO diet status admitted to an academic medical center between 2001 and 2016. Clinical documentation was reviewed. Antiepileptic drug selection (medication and route of administration) and presence or absence of seizures were recorded. Results: We identified 199 admissions during which epilepsy patients had NPO diet orders. Antiepileptic drug management strategies included continuation of oral medications (50.3% of admissions), intravenous AED monotherapy (22.1%), intravenous AED polytherapy (12.6%), benzodiazepines (1.0%), holding AEDs (4.5%), or a combination (9.5%). Seizures occurred during 14 admissions. Treatment with AED polytherapy prior to admission and changing the patient's AED regimen during admission were associated with increased odds of seizures during admission ( P = .0028; P = .0114). Conclusions: These results suggest that patients' home oral AED regimens should be continued when possible in order to minimize the frequency of seizures during hospitalizations.